RANCANGAN SISTEM PEMBAYARAN PADA CHOPPER STEAK & CAFE DENGAN MENGGUNAKAN VISUAL FOXPRO 9.0 - Ratna Septiani; Elly Agustina (Jurnal Sistem Informasi, 2010)
The design of payment systems on Chopper Steak & Cafe is designed for ease incarrying out payment transactions so that the process becomes more effectiveand efficient. The design of the payment system made by Delphi ProgrammingLanguage Visual FoxPro 9.0, because by using Visual FoxPro 9.0 ProgrammingLanguage designed to be easy to use various facilities provided by the MicrosoftVisual Foxrpo. So that can assist in the administration of the Chopper steak &Cafe and can facilitate in the implementation process transactions and reportcreation process becomes more efficient.